Glass Ceilings, Glass Hammers and Glass Escalators: Is it time for a break-through? - Connell, Julia; Chang, Joshua; Travaglione, Tony; Burgess, John (British Academy of Management (BAM), 2012)
It has been widely reported that women experience a gender income gap, earning on average approximately 18 per cent less than men. OECD statistics indicate that the proportion of women in paid work is high at 62 per cent across OECD countries, that one-third of managerial posts are held by women and that many more women than men work in part-time jobs (25% and 6% respectively). When women have children, the gender differences are found to be even greater, given more women than men take on the major child care responsibilities. This paper explores the topics of ‘income’, ‘position’, ‘employment status’, and ‘dependent children’ among the men and women of the Australian workforce comparing findings from the Australia at Work data with OECD data. As the title of the paper implies, where income is concerned, Australian women have to grapple with ‘glass ceilings’ while Australian men can frequently step onto a ‘glass escalator’. The paper discusses the implications of these gender inequalities for the Australian workforce, reports on current initiatives intended to address them, and provides suggestions regarding how the gaps may be able to be reduced.